Negative campaigning, issue salience and vote choice: assessing the effects of the Australian Labor party's 2016 "Mediscare" campaign. Issue 1 (2nd January 2020) - Carson, Andrea; Martin, Aaron J.; Ratcliff, Shaun
ABSTRACT: This study contributes to the scholarship on negative campaigning, revealing the important dynamics of party and media messaging and its subsequent effects on issue salience and vote choice. Using a large-scale dataset combined with content analysis of media coverage and party press releases, we offer an innovative methodology that provides evidence showing the effect of a prominent negative campaign ("Mediscare") launched by the centre-left Australian Labor Party during Australia's 2016 federal election. We find political elites can influence what voters are paying attention to and, when issue salience is high, this can influence vote choice. We find Labor's "Mediscare" had two main effects. It significantly raised the issue salience of healthcare with voters, and it had an impact on vote choice, particularly in marginal electorates. The scare campaign providing a reinforcement effect for Labor, arresting declining support for the party that was evident prior to the commencement of the negative campaign. We conclude that under the circumstances of high public awareness, "issue ownership" and compulsory voting, this negative campaign was effective in shaping the 2016 electoral outcome.